Stigma and associated sex disparities among patients with tuberculosis in Uganda: a cross-sectional study - Juliet N. Sekandi; Trang Quach; Ronald Olum; Damalie Nakkonde; Leila Farist; Rochelle Obiekwe; Sarah Zalwango; Esther Buregyeya (Therapeutic Advances in Infectious Disease)
Background: Tuberculosis (TB) is the leading cause of death from a single infectious agent globally. The stigma associated with TB, encompassing self, anticipated, and public stigma, has significant negative effects on treatment adherence. In Uganda, limited data exist on the prevalence of stigma and its relationship with sex among patients with TB. Objectives: We aimed to evaluate the prevalence of three types of stigma and their relationship with the sex of patients undergoing TB treatment. Design: Cross-sectional study. Methods: This cross-sectional study was conducted among patients living with TB attending selected TB clinics in Kampala, Uganda, between July 2020 and March 2021. We collected data on sociodemographics and used 13 items to capture the self, anticipated, and public stigma from which we composed the dependent variables. We employed multivariable logistic regression analysis to evaluate the association between sex and the three stigma types. Additionally, we considered potential confounders such as age, HIV, and employment status. Statistical significance was defined as p  < 0.05. Results: In this study, we enrolled 144 participants with a mean age of 35.8 years (standard deviation = 12). Half of the participants were female, 44.4% had a secondary education, 37.5% were unemployed, and 32.6% were living with both HIV and TB. The prevalence of self-stigma was 71.1%, anticipated stigma was 75.7%, and public stigma was 41.7%. Significant factors associated with self-stigma were female sex (adjusted odds ratio (AOR): 2.35, 95% confidence interval (CI): 1.02–5.74) and unemployment (AOR: 2.95, 95% CI: 1.16–8.58). Living with HIV was significantly associated with anticipated stigma (AOR: 3.58, 95% CI: 1.38–11.23). However, none of the evaluated variables showed a significant association with public stigma. Conclusion: Our study showed a relatively high prevalence of self, anticipated, and public stigma among TB patients. Notably, females and unemployed individuals were at a higher risk of self-stigma, while those with HIV/AIDS and TB were more likely to report anticipated stigma. To combat stigma effectively, interventions should be tailored to cater to sex-specific needs and persons living with HIV. Future research should delve further into determinants of TB-related stigma in high-burden settings.